PW 1702 Swedisch vision zero policies for safety – a comparative policy content analysis. (November 2018) - Kristianssen, Ann-Catrin; Andersson, Ragnar; Belin, Matts-Åke; Nilsen, Per
Abstract : The Vision Zero policy was adopted by the Swedish parliament in 1997 as a new direction for road traffic safety. The aim of the policy is that no one should be killed or seriously injured due to traffic accidents and that the design of the road transport system should be adapted to those requirements. Vision Zero has been described as a policy innovation with a focus on the tolerance of the human body to kinetic energy and that the responsibility for road safety ultimately falls on the system designers. In Sweden, the Vision Zero terminology has spread to other safety-related areas, such as fire safety, patient safety, workplace safety and suicide. The purpose of this article is to analyze, through a comparative content analysis, each Vision Zero policy by identifying the policy decision, policy problem, policy goal, and policy measures. How a policy is designed and formulated has a direct effect on implementation and outcome. The similarities and differences between the policies give an indication of the transfer method in each case. The results show that the Vision Zero policies following the Vision Zero for road traffic contain more than merely a similar terminology, but also that the ideas incorporated in Vision Zero are not grounded within each policy area as one would expect. The study show that it is easier to imitate formulations in a seemingly successful policy and harder to transform Vision Zero into a workable tool in each policy area.